2016
DOI: 10.1073/pnas.1607051113
|View full text |Cite
|
Sign up to set email alerts
|

Practice improves peri-saccadic shape judgment but does not diminish target mislocalization

Abstract: Visual sensitivity is markedly reduced during an eye movement. Peri-saccadic vision is also characterized by a mislocalization of the briefly presented stimulus closer to the saccadic target. These features are commonly viewed as obligatory elements of perisaccadic vision. However, practice improves performance in many perceptual tasks performed at threshold conditions. We wondered if this could also be the case with peri-saccadic perception. To test this, we used a paradigm in which subjects reported the orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 78 publications
4
6
0
Order By: Relevance
“…Each participant was randomly assigned to one of five groups (n ¼ 10 each): four training groups that were tested at least five times and one control group that was tested at least twice (see Table 1). Sample size per group is comparable to other studies investigating training effects on eye or finger movements (Dempsey-Jones et al, 2016;Porat & Zohary, 2016). Remuneration was $8 per hour for each session; a bonus of $20 was paid upon completion of all five sessions.…”
Section: Participantsmentioning
confidence: 89%
See 1 more Smart Citation
“…Each participant was randomly assigned to one of five groups (n ¼ 10 each): four training groups that were tested at least five times and one control group that was tested at least twice (see Table 1). Sample size per group is comparable to other studies investigating training effects on eye or finger movements (Dempsey-Jones et al, 2016;Porat & Zohary, 2016). Remuneration was $8 per hour for each session; a bonus of $20 was paid upon completion of all five sessions.…”
Section: Participantsmentioning
confidence: 89%
“…On the other hand, specificity depends on stimulus characteristics and task requirements. Transfer of perceptual learning from one location to another has been observed when the second location was previously sensitized via training an irrelevant task at that location (Xiao et al, 2008) or when the same stimuli were used (Porat & Zohary, 2016). Transfer across tasks, for example, from Vernier acuity and contrast detection to Snellen acuity, has been observed in patients with amblyopia (Levi & Li, 2009) and college baseball players (Deveau, Ozer, & Seitz, 2014), who even seem to improve on-field performance following such training (see also Faubert, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that perceptual learning is possible both before ( 48 ) and during ( 49 ) saccades. Porat and Zohary ( 49 ) demonstrated that shape discrimination could improve, even if the stimulus was presented during a saccade.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical validation of this assumption is lacking, however, as most studies aggregate perisaccadic visual judgements (often in a small number of well-trained observers) across multiple testing sessions. Two recent studies have reported learned improvements in visual task performance following training with stimuli consistently presented before ( 48 ) or during ( 49 ) saccades. While these findings demonstrate that perceptual learning is possible around the time of saccades, the role of suppression in this process remains unclear.…”
mentioning
confidence: 99%
“…One exception is the learning of new visual associations between stimuli seen across saccades (40)(41)(42)(43), but in most cases it does not appear that saccades are necessary to elicit this type of learning (39)(40)(41). Other studies have shown that perceptual learning is sensitive to spatiotopic locations defined in part by eye position (44) and that perceptual learning can improve visual sensitivity during saccades (45).…”
Section: Discussionmentioning
confidence: 99%